Robust critical values for unit root tests for series with conditional heteroscedasticity errors: An application of the simple NoVaS transformation - Panagiotis Mantalos (Örebro University School of Business, 2012)
In this paper, we introduce a set of critical values for unit root tests that are robust in the presence of conditional heteroscedasticity errors using the normalizing and variance-stabilizing transformation (NoVaS) in Politis (2007) and examine their properties using Monte Carlo methods. In terms of the size of the test, our analysis reveals that unit root tests with NoVaS-modified critical values have actual sizes close to the nominal size. For the power of the test, we find that unit root tests with NoVaS-modified critical values either have the same power as, or slightly better than, tests using conventional Dickey–Fuller critical values across the sample range considered.
Keywords: C01; C12; C15; 330; Critical values; normalizing and variance-stabilizing transformation; unit root tests